Solve the initial-value problem: (dx/dt)+(tant)x=(cost)^2, x(0)=-1.
Substitution:
"x(t) = u(t)v(t) \\Rightarrow \\frac{{dx}}{{dt}} = x' = u'v + uv'"
Then
"u'v + uv' + uv\\tan t = {\\cos ^2}t"
"u'v + u\\left( {v' + v\\tan t} \\right) = {\\cos ^2}t"
Let
"v' + v\\tan t = 0 \\Rightarrow \\frac{{dv}}{{dt}} = - v\\tan t \\Rightarrow \\frac{{dv}}{v} = - \\frac{{\\sin t}}{{\\cos t}}dt = \\frac{{d\\cos t}}{{\\cos t}} \\Rightarrow \\ln v = \\ln \\cos t \\Rightarrow v = \\cos t"
Then
"u'\\cos t = {\\cos ^2}t \\Rightarrow u' = \\cos t \\Rightarrow u = \\sin t + C"
Then
"x = uv = \\left( {\\sin t + C} \\right)\\cos t"
"x(0) = - 1 \\Rightarrow (\\sin 0 + C)\\cos 0 = - 1 \\Rightarrow C = - 1"
Answer: "x = \\left( {\\sin t - 1} \\right)\\cos t"
Comments
Leave a comment